Biological Abundance and Diversity in Organic-Rich Sediments From a Florida Barrier Island Lagoon - Fuller, Kate M.; Fox, Austin L.; Jacoby, Charles A.; Trefry, John H. (Frontiers in Marine Science, 2021)
Organic-rich sediments in estuaries and the coastal ocean and are a product of land clearing, runoff of excess nutrients and other human activities. They harbor pollutants, oxygen-consuming microbes and toxic hydrogen sulfide (H2S), thereby creating a hostile environment for infauna. In one barrier island lagoon, the Indian River Lagoon (IRL), Florida, layers of organic-rich sediments have increased substantially in thickness and areal extent over the past 60 years. Geochemical properties of these muddy sediments have been described; however, less is known about their habitability. We analyzed infauna and geochemical properties of 102 samples taken during wet and dry seasons at 17 locations spanning 60 km of the lagoon. We quantified infaunal abundance and diversity (Shannon-Wiener, H′) and determined Pearson’s correlation coefficients for effective number of species (ENS = eH′) versus sediment porosity (ɸ = 0.69‒0.95), organic carbon (1‒8%), nitrogen (0.1‒0.7%), silt + clay (16‒99%), porewater H2S (5‒3600 μM) and other environmental variables. Small bivalves accounted for 70% of the organisms collected, followed by gastropods, polychaetes and other biota. The bivalves were predominantly Macoma spp., Mulinia lateralis and Parastarte triquetra with average abundances of 3,896, 2,049, and 926 individuals per m2, respectively. High abundance of some species, such as Macoma, showed that these opportunists had adapted to poor quality sediments. More than two-thirds of the 35 species collected were present at <100 individuals per m2 of sediment. Cluster analysis identified four groups of stations with significantly different geochemical properties. Permutation analyses of variance indicated that the four groups also (represented, delineated?) statistically different infaunal communities. Diversity decreased with increasing sediment concentrations of carbon, nitrogen and silt + clay; however, community richness at our most prolific station along the perimeter of muddy deposits was ~7 times lower than found previously in sandy sediments from the IRL. The results identified areas where infaunal communities have experienced the greatest stress due to accumulation of organic-rich sediments. Results from this study help support management plans for remediation of organic-rich mud and improvement of sediment and water quality, especially in areas identified with low ENS.